(untitled) (Editora Impacto Científico, 2025)
The p53 gene is considered the "guardian of the genome", a protein located in the position 1.3 of the short arm of chromosome 17, whose main function maintaining genome stability under normal conditions and also its integrity. The p53 by having the function of preserving genome integrity, assigns a significant role in carcinogenesis, their relationship has been established due to the high rate of mutations found in malignant tumors from different tissues. Its performance in almost all human tumors, directly or indirectly, has been observed in the pathogenesis. When stabilized, p53 is converted into a functional protein due to its translational modifications in response to cellular stress derived from DNA damage, which follows the start of the realization of some functions due to genetic damage, such as particularly in genes that regulate the cell cycle, DNA stability and programmed cell death (apoptosis). DOI: https://doi.org/10.56238/edimpacto2025.087-005